2012
DOI: 10.1002/adfm.201103067
|View full text |Cite
|
Sign up to set email alerts
|

Model Organic Surfaces to Probe Marine Bacterial Adhesion Kinetics by Surface Plasmon Resonance

Abstract: Understanding how bacteria adhere to a surface is a critical step in the development of novel materials and coatings to prevent bacteria forming biofilms. Here, surface plasmon resonance (SPR) spectroscopy, in combination with self‐assembled monolayers (SAMs) that have different backbone structures and/or functional groups, is used for the first time to study the initial stages of bacterial adhesion to surfaces (i.e., initial interaction of cells with a surface, a process governed by van der Waals, electrostat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 56 publications
3
42
0
Order By: Relevance
“…Although no comprehensive studies on the influence of polymer charge on the attachment of cells of C. marina have been reported yet, Pranzetti et al (Pranzetti et al 2012) demonstrated higher attachment of cells of C. marina (1 h exposure) on positively charged amine-terminated SAMs than on neutral (methyl-, EG6-or hydroxyl-terminated) SAMs, which is in accordance with our current results. It has also been reported (Ista et al 1996, Ista et al 1999) that cells of C. marina have a higher affinity for hydrophobic surfaces (2 h exposure).…”
Section: Fouling Assayssupporting
confidence: 83%
“…Although no comprehensive studies on the influence of polymer charge on the attachment of cells of C. marina have been reported yet, Pranzetti et al (Pranzetti et al 2012) demonstrated higher attachment of cells of C. marina (1 h exposure) on positively charged amine-terminated SAMs than on neutral (methyl-, EG6-or hydroxyl-terminated) SAMs, which is in accordance with our current results. It has also been reported (Ista et al 1996, Ista et al 1999) that cells of C. marina have a higher affinity for hydrophobic surfaces (2 h exposure).…”
Section: Fouling Assayssupporting
confidence: 83%
“…41 The final stage of the protocol involved two washes of the cells in filtered ASW to remove excess extracellular polymeric substances that interfere with cell attachment. 42 The final bacterial suspension had an OD600nm = 0.1 (4 x 10 7 cells/ml). The slides were placed in polystyrene Quadriperm dishes (Greiner Bio-One Ltd.) and 10 mL of bacterial suspension were added to each well.…”
mentioning
confidence: 99%
“…These switchable surfaces are playing an increasingly important part in the development of highly sensitive biosensors [85], novel drug delivery systems [148] and highly functional microfluidic [277], bioanalysis [278], and bioseparation [279] systems. Additionally, dynamic, synthetic surfaces that can control the presentation of regulatory signals [220,280] to a cell are expected to have a significant impact in tissue engineering [176] and regenerative medicine [208], and to provide unprecedented opportunities in fundamental studies of cell biology.…”
Section: Resultsmentioning
confidence: 99%